الدلالة الاجتماعية في كلمات "فرقة وطائفة وقوم" في كتاب إشارات الإعجاز في مظان الإيجاز لبديع الزمان سعيد النورسي - Addakhil, Abdurrahman; Buana, Cahya (Litteratura: Jurnal Bahasa dan Sastra, 2023)
Bediuzzaman Said Nursi is a scholar and Sufi thinker who has compiled many books collected in Rasāil al-Nūr. One of the books in the diwan is Isyārāt al-I'jāz fī Maẓān al-Ījāz which focuses on the interpretation of the Qur'an. This study aims to determine the contextual meaning of the words firqah, ṭaifah, and qaum in the book Isyārāt al-I'jāz fī Maẓān al-Ījāz, as well as the semantic and social relationships between the three words in terms of meaning fields and meaning components. To achieve this goal the research used a qualitative method using semantic theory to analyze it. Furthermore, the results of this study indicate that: 1) The contextual meaning of the word firqah is (a'ṭinā), ṭaifah is (waffiqnā) both of which are included in the context of asking for guidance, and qaum is anna khāṣiyat al hayāt kamā marra tuṣayyiru al-juz'a kullan wa al- munfarida jama'atan wa al-muqayyad muṭlaqan wa al-farda 'ālaman, or with another meaning ja'l al-mustawā al-aṣgar ila al-juz al-akbar wa al-syay al-juz'iy yuṣbih syāmilan and all of these contextual meanings include siyāq al-mawqif. 3) The meaning fields of the three words are incorporated into the type of social group, and the components of the same meaning are al-ism, al-rijāl, al,nisā,al-nās, and al-jamā'ah. The components of different meanings are al-ṣaf, al-'adad, al-qiṭ'ah, al-jays, al-juz, al-wahdah al-taṣnifiyah, arba'ah anfus, and al-'ibād. The equivalent of the term firqah is communal, ṭaifah is community, and qaum is society.